Study of the Concept of Ashabiyah Ibnu Khaldun in the Development of Human Resources for Modern Economic Development - Meilinda, Shinta; Pelitawati, Eva; wartoyo, Wartoyo (Sekolah Tinggi Agama Islam Kuningan, 2025)
Ibn Khaldun, as one of the early figures in the disciplines of economics, sociology, and the philosophy of history, emphasized the importance of integrating spiritual, social, and intellectual values in the human development process. Process. In Muqaddimah, he describes the relationship between the quality of human resources, social cohesion (asabiyyah), the education system based on adab, and the state’s role in creating a sustainable civilization. This research aims to examine Ibn Khaldun's thoughts on human resource development (HRD) and relate them in the context of the modern economic development paradigm. This research employs a qualitative approach, utilizing the method of literature study and critical analysis. The study found that Ibn Khaldun's thought is very highly relevant to addressing the challenges of human resource development in the era of globalization. The results of the study reveal that the integrative model between Ibn Khaldun's thought and modern economics comprises seven main pillars: transcendental values, holistic education, social cohesion, lifelong learning, a balanced role of the state and the market, a multidimensional measurement system, and fair institutional governance. Thus, this research recommends an approach to human resource development that is not merely economically oriented, but also integrates moral, social, and spiritual aspects to create sustainable and civilized development.